A look at childhood and youth as seen in the television of the nineties (2004)
The nineties begin with a new political Constitution, the one of 1991. From the viewpoint of culture and education this event had defining consecuences on the development of a new idea of nation, such as the clear recognition of freedom of choice as an inalienable right for individuals, including youngsters. During this decade Colombian television was attentive to the problems of youth and develops successful stories about them. This interest is possibly related to the social climate due to the political changes. Additionaly these fictional Colombian stories interpret reality in a more interesting manner that newscasts and documentaries. This article peruses the television programs of the nineties in order to discover tendencies than address two topics: programs for youngsters and themes that deal with reality.